Property Protection in the Event of a Fire - Petterson, Carl; Menzemer, Leo Willem ; 0000-0001-5348-1520; Hejtmanek, Petr; Brandon, Daniel (Springer Tracts in Civil Engineering, 2025)
Timber buildings present unique fire safety challenges compared to non-combustible constructions. Fire damage in timber structures includes smoke, heat-related impacts and firefighting water. Effective fire mitigation strategies, such as smoke detection systems, automatic suppression systems, and compartmentation, can be crucial for enabling timely interventions and minimizing damages. Post-fire restoration focuses on water extraction, removal of smoke damage and replacing contaminated material as well as structural repairs. Modern timber buildings will more often than not require expert input to safely and effectively open or remove structural elements to allow necessary restoration. This chapter highlights the need for collaboration, innovative fire safety measures, and efficient restoration processes to improve the property protection in timber buildings. This is a field where further research is essential to address the evolving challenges of timber construction and enhance its sustainability.